Structures and Divergent Mechanisms in Capsid Maturation and Stabilization Following Genome Packaging of Human Cytomegalovirus and Herpesviruses - Clotilde Muller; Sophie Alain; Thomas F. Baumert; Gaëtan Ligat; Sébastien Hantz (Life, 2021)
Herpesviruses are the causative agents of several diseases. Infections are generally mild or asymptomatic in immunocompetent individuals. In contrast, herpesvirus infections continue to contribute to significant morbidity and mortality in immunocompromised patients. Few drugs are available for the treatment of human herpesvirus infections, mainly targeting the viral DNA polymerase. Moreover, no successful therapeutic options are available for the Epstein–Barr virus or human herpesvirus 8. Most licensed drugs share the same mechanism of action of targeting the viral polymerase and thus blocking DNA polymerization. Resistances to antiviral drugs have been observed for human cytomegalovirus, herpes simplex virus and varicella-zoster virus. A new terminase inhibitor, letermovir, recently proved effective against human cytomegalovirus. However, the letermovir has no significant activity against other herpesviruses. New antivirals targeting other replication steps, such as capsid maturation or DNA packaging, and inducing fewer adverse effects are therefore needed. Targeting capsid assembly or DNA packaging provides additional options for the development of new drugs. In this review, we summarize recent findings on capsid assembly and DNA packaging. We also described what is known about the structure and function of capsid and terminase proteins to identify novels targets for the development of new therapeutic options.